Molecular genetic findings in small bowel neuroendocrine neoplasms: a review of the literature. (May 2015) - Miller, Helen C; Kidd, Mark; Castellano, Leandro; Frilling, Andrea
Small bowel neuroendocrine neoplasms (SBNEN) are the most common small bowel tumor and have an increasing incidence. Despite many treatment options, therapeutic strategy remains a key clinical challenge due to the paucity of large-scale, randomized controlled trials. The heterogeneity of SBNEN coupled with a lack of detailed information about the tumor biology, impedes patient stratification into groups based on tumor phenotypes or treatment response. More detailed analysis of the genetic and epigenetic characteristics of SBNEN, will allow treatment to move toward a more personalized medicine approach through the identification of novel biomarkers and therapeutic targets, with the aim to increase survival.